Correction to: Important drivers of East African monsoon variability and improving rainy season onset prediction - Indrani Roy; Meshack Mliwa; Alberto Troccoli (Natural Hazards, 2024)

Integrative characterization and phylogenetic relationships of Xiphinema rivesi and X. pachtaicum (Nematoda, Longidoridae) associated to vineyards in North Italy - Alberto Troccoli; Alessio Vovlas; Elena Fanelli; Valentina Papeschi; Stefano Toninelli; Trifone D’Addabbo; Francesca De Luca (European Journal of Plant Pathology, 2024)

Identifying important drivers of East African October to December rainfall season - Indrani Roy; Alberto Troccoli (Science of The Total Environment, 2024)

Important drivers of East African monsoon variability and improving rainy season onset prediction - Indrani Roy; Meshack Mliwa; Alberto Troccoli (Natural Hazards, 2024)
Monsoon rain and its year-to-year variability have a profound influence on Africa’s socio-economic structure by heavily impacting sectors such as agricultural and energy. This study focuses on major drivers of the east African monsoon during October-November-December (OND) which is the standard time window for the onset of the rainy season, be it unimodal or bimodal. Two drivers viz. Indian Ocean Dipole (IOD) and El Niño Southern Oscillation (ENSO) both separately indicate very strong positive connections with monsoon (OND) rain not only in the OND season with zero seasonal lag, but the signal is also present even taking IOD and ENSO a season ahead. A compositing approach is applied that can additionally identify strong signals when different combinations of ENSO and IOD phases act as confounding factors. Results of precipitation anomaly suggest that when IOD and ENSO are both on the same phase in July-August-September (JAS), a significant OND rainfall anomaly occurs around the east African sector: A deficit (excess) of OND monsoon rain occurs when both drivers are in a negative (positive) phase during JAS. A location Kibaha in Tanzania, for which station data are available, is considered for a more in-depth analysis. The uncertainty range in cumulative OND rainfall is also reduced to a large degree when IOD and ENSO phases are both negative in JAS. These results can be used for prediction purposes and interestingly, that criterion of IOD and ENSO being of same phase in JAS was again matched in 2022 (both negative) and hence it was possible to deliver early warnings for a deficit in rainfall a season ahead. Techniques to compute the monsoon onset as determined by meteorological services such as the Tanzania Meteorological Authority rely on various thresholds, which may also vary by country. To overcome some of the issues with thresholds-based techniques, other definitions of ‘onset’ take into account cumulative rainfall amount and such technique has also been tested and compared. In both approaches, late (early) onsets dominate in years when ENSO and IOD are both negative (positive) during JAS. In these cases, it is therefore possible to provide an estimation of cumulative rainfall and onset for OND in terms of average, median value, range and distribution of rainfall one season in advance. Such results have implications for optimizing agricultural, water and energy management, also mitigating possible severe production losses, which would impact the livelihoods of millions of Africans.

Occurrence of Cryptaphelenchus minutus and other nematode species associated with the bark of unidentified coniferous tree in Italy - Elena Fanelli; Alberto Troccoli; Stefano Sacchi; Pablo Castillo; Francesca Gaffuri; Beniamino Cavagna; Francesca De Luca (European Journal of Plant Pathology, 2022)

Characterisation of Aceria massalongoi and a histopathological study of the leaf galls induced on chaste trees - Enrico de Lillo; Elena Fanelli; Domenico Valenzano; Rosita Monfreda; Alberto Troccoli; Alessio Vovlas; Francesca De Luca (Experimental and Applied Acarology, 2020)

Introducing the Bulletin of Atmospheric Science and Technology - Paolo Di Girolamo; Silvana Di Sabatino; Cristina Lozej Archer; Carlo Buontempo; Simona Bordoni; Giorgio Budillon; Andrea Buzzi; Domenico Cimini; Gabriele Curci; Joan Cuxart; Silvio Davolio; Rossella Ferretti; et al. (Bulletin of Atmospheric Science and Technology, 2020)

Molecular variability of the root-lesion nematode, Pratylenchus loosi (Nematoda: Pratylenchidae), from tea in Iran - Seyedeh Negin Mirghasemi; Elena Fanelli; Alberto Troccoli; Salar Jamali; Mohammed Mehdi Sohani; Francesca De Luca (European Journal of Plant Pathology, 2019)

Morpho-molecular characterization of Ditylenchus gigas and D. oncogenus parasitizing broad bean, Vicia faba, in Algeria - Ines Saadi; Francesca De Luca; Elena Fanelli; Alberto Troccoli; Nicola Greco; Halima Benbouza (European Journal of Plant Pathology, 2019)

Correction to: Sequence variation in ribosomal DNA and in the nuclear hsp90 gene of Pratylenchus penetrans (Nematoda: Pratylenchidae) populations and phylogenetic analysis - Elena Fanelli; Alberto Troccoli; Francesco Capriglia; Giuseppe Lucarelli; Nicola Vovlas; Nicola Greco; Francesca De Luca (European Journal of Plant Pathology, 2018)

Sequence variation in ribosomal DNA and in the nuclear hsp90 gene of Pratylenchus penetrans (Nematoda: Pratylenchidae) populations and phylogenetic analysis - Elena Fanelli; Alberto Troccoli; Francesco Capriglia; Giuseppe Lucarelli; Nicola Vovlas; Nicola Greco; Francesca De Luca (European Journal of Plant Pathology, 2018)

Histopathology of Dryas octopetala leaves co-infected by Subanguina radicicola and Aphelenchoides sp. and molecular caracterization of the nematodes - Elena Fanelli; Alberto Troccoli; Nicola Vovlas; Keith Bland; Francesca De Luca (European Journal of Plant Pathology, 2018)

Detection and molecular characterization of the rice root-knot nematode Meloidogyne graminicola in Italy - Elena Fanelli; Alba Cotroneo; Loredana Carisio; Alberto Troccoli; Silvio Grosso; Cristina Boero; Francesco Capriglia; Francesca De Luca (European Journal of Plant Pathology, 2017)

Potential impacts of solar arrays on regional climate and on array efficiency - Kim C. Nguyen; Jack J. Katzfey; John Riedl; Alberto Troccoli (International Journal of Climatology, 2017)
World population and industrialization have increased significantly, leading to an increase in global energy demand, mainly relying on fossil fuels. Use of alternative energy sources such as wind, hydro and solar has been steadily increasing. Australia is a vast continent which receives an average 58 million PJ of energy from the sun annually. Given this resource potential, one could envisage construction of massive solar farms to help meet energy demands. If such constructions went ahead, their potential benefits/impacts on the climate over and surrounding the solar arrays would need to be investigated. Here, we study the potential climatic impacts over and in the environment surrounding massive hypothetical solar sites across Australia using a global stretched grid atmospheric model. The solar farms are represented by modelling the effects of perturbing surface albedo and surface roughness. The sensitivity experiments incorporate different combinations of surface albedos, shapes and locations of the solar farms, with a focus on the summer season. Our study suggests that depending on array sizes, locations, orientations and surface albedo (potentially increased by means of highly reflective in‐fill material), the climate over solar arrays could be modified significantly. Over the arrays with positive albedo perturbation, rainfall would decrease by around 30–70%, and daytime maximum air temperatures would decrease up to 10 °C. In addition, solar irradiance would increase by around 5–20%, which combined with the air temperature cooling, would lead to an enhanced solar power yield up to 25%.

Erratum to: “Morphological and molecular identification of potato and cereal cyst nematode isolates from Algeria and their phylogenetic relationships with other populations from distant geographical areas” - Nadia Tirchi; Alberto Troccoli; Elena Fanelli; Aissa Mokabli; Fazia Mouhouche; Francesca De Luca (European Journal of Plant Pathology, 2017)

Morphological and molecular identification of potato and cereal cyst nematode isolates from Algeria and their phylogenetic relationships with other populations from distant theirgeographical areas - Nadia Tirchi; Alberto Troccoli; Elena Fanelli; Aissa Mokabli; Fazia Mouhouche; Francesca De Luca (European Journal of Plant Pathology, 2016)

Description of a new needle nematode, Longidorus asiaticus n. sp. (Nematoda: Longidoridae), from the rhizosphere of crape myrtle (Lagerstroemia indica) bonsai trees imported into Italy from China - Nicola Trisciuzzi; Antonio Archidona-Yuste; Alberto Troccoli; Elena Fanelli; Francesca De Luca; Nicola Vovlas; Pablo Castillo (European Journal of Plant Pathology, 2015)

Detection of the camellia root-knot nematode Meloidogyne camelliae Golden in Japanese camellia bonsai imported into Italy: integrative diagnosis, parasitic habits and molecular phylogeny - Nicola Trisciuzzi; Alberto Troccoli; Nicola Vovlas; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2014)

Heterodera elachista the Japanese cyst nematode parasitizing corn in Northern Italy: integrative diagnosis and bionomics - Francesca De Luca; Nicola Vovlas; Giuseppe Lucarelli; Alberto Troccoli; Vincenzo Radicci; Elena Fanelli; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2013)

Morphological and molecular characterisation of Xiphinema macroacanthum Lamberti, Roca & Agostinelli, 1989 (Nematoda: Longidoridae) from olive orchards in southern Italy - Francesca De Luca; Stela Lazarova; Alberto Troccoli; Nicola Vovlas; Vlada Peneva (Systematic Parasitology, 2013)

Integrative diagnosis and parasitic habits of Cryphodera brinkmani a non-cyst forming heteroderid nematode intercepted on Japanese white pine bonsai trees imported into Italy - Nicola Vovlas; Nicola Trisciuzzi; Alberto Troccoli; Francesca De Luca; Carolina Cantalapiedra-Navarrete; Pablo Castillo (European Journal of Plant Pathology, 2013)

Reply to comment on “Storm surge frequency reduction in Venice under climate change” by G. Jordà, D. Gomis & M. Marcos - Alberto Troccoli; Filippo Zambon; Kevin I. Hodges; Marco Marani (Climatic Change, 2012)

Storm surge frequency reduction in Venice under climate change - Alberto Troccoli; Filippo Zambon; Kevin I. Hodges; Marco Marani (Climatic Change, 2012)

Molecular variability and phylogenetic relationships among different species and populations of Pratylenchus (Nematoda: Pratylenchidae) as inferred from the analysis of the ITS rDNA - Francesca De Luca; Aurelio Reyes; Alberto Troccoli; Pablo Castillo (European Journal of Plant Pathology, 2011)

Molecular phylogeny of the genus Rotylenchus (Nematoda, Tylenchida) and description of a new species - Nicola Vovlas; Sergei A. Subbotin; Alberto Troccoli; Gracia Liébanas; Pablo Castillo (Zoologica Scripta, 2008)
A description of a new species of plant parasitic nematodes of the genus Rotylenchus from the family Hoplolaimidae is given and a recognition of Rotylenchus jaeni comb. n., previously known as subspecies R. magnus jaeni, as separate species is proposed. Rotylenchus montanus sp. n. is characterized by a hemispherical lip region with six rarely seven annuli, stylet 33–37 µm, female tail rounded, regularly annulated tip with 12–18 annuli and phasmid located 2–9 annuli anterior to anus. Rotylenchus montanus sp. n. is close to species of the monosexual group R. arsenjevi , R. corsicus , R. fragaricus , R. helicus , R. indorobustus and R. neorobustus , by a number of specific characteristics resulting from its specific matrix code: A5, B1, C1, D4, E2, F2, G3, H2, I2, J2, K2. Molecular characterization of R. montanus sp. n. and other Rotylenchus species are provided using D2–D3 expansion segments of 28S and the ITS1 of rRNA genes. The D2–D3 of 28S rRNA and the ITS1–rRNA sequences of R. montanus sp. n. differed in one nucleotide and in 16–20 nucleotides from those of an unidentified Rotylenchus species from Russia, respectively. Molecular analysis of populations of R. magnus and R. jaeni comb. n. demonstrated differences in the D2–D3 and the ITS1–rRNA sequences. These genetic differences together with some minor morphological characters support that both subspecies should be considered as two cryptic sibling species and warranted their elevation to species rank. The result of phylogenetic analysis of Hoplolaimidae for 45 sequences of the D2 and D3 expansion regions of 28S rRNA gene using Bayesian inference analysis under the complex model is presented. Phylogenetic tree of Rotylenchus species represents seven moderate to highly supported lineages. Grouping of Rotylenchus species within other hoplolaimids and analysis of phylogenetic relationships within the genus Rotylenchus using the ITS1 of rRNA gene sequences are also discussed.